Drought Legacy in Sub‐Seasonal Vegetation State and Sensitivity to Climate Over the Northern Hemisphere - Minchao Wu; Stefano Manzoni; Giulia Vico; Ana Bastos; Franciska T. deVries; Gabriele Messori (Geophysical Research Letters)
Abstract Droughts affect ecosystems at multiple time scales, but their sub‐seasonal legacy effects on vegetation activity remain unclear. Combining the satellite‐based enhanced vegetation index MODIS EVI with a novel location‐specific definition of the growing season, we quantify drought impacts on sub‐seasonal vegetation activity and the subsequent recovery in the Northern Hemisphere. Drought legacy effects are quantified as changes in post‐drought greenness and sensitivity to climate. We find that greenness losses under severe drought are partially compensated by a ∼+5% greening within 2–6 growing‐season months following the droughts, both in woody and herbaceous vegetation but at different timings. In addition, post‐drought sensitivity of herbaceous vegetation to hydrological conditions increases noticeably at high latitudes compared with the local normal conditions, regardless of the choice of drought time scales. In general, the legacy effects on sensitivity are larger in herbaceous vegetation than in woody vegetation.